2007
DOI: 10.1093/cercor/bhm217
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin Receptor Involvement in the Rise of Extracellular Glutamate Levels and Apoptotic Nerve Cell Death in Primary Cortical Cultures after Oxygen and Glucose Deprivation

Abstract: In view of the ability of neurotensin (NT) to increase glutamate release, the role of NT receptor mechanisms in oxygen-glucose deprivation (OGD)-induced neuronal degeneration in cortical cultures has been evaluated by measuring lactate dehydrogenase (LDH) levels, mitochondrial dehydrogenase activity with 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide levels, and microtubule-associated protein 2 (MAP2) immunoreactivity. Apoptotic nerve cell death was analyzed measuring chromatin condensation with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…1A); additionally, apoptotic neurons showed reduced and irregular MAP2 staining (Fig. 1A), consistent with previous observations (51)(52)(53)(54). This approach revealed that tatCN21 significantly reduced glutamate-induced neuronal death, indicating that CaMKII stimulation promotes excitotoxicity (Fig.…”
Section: Tatcn21 Protects Neurons From Excitotoxic Death-supporting
confidence: 91%
“…1A); additionally, apoptotic neurons showed reduced and irregular MAP2 staining (Fig. 1A), consistent with previous observations (51)(52)(53)(54). This approach revealed that tatCN21 significantly reduced glutamate-induced neuronal death, indicating that CaMKII stimulation promotes excitotoxicity (Fig.…”
Section: Tatcn21 Protects Neurons From Excitotoxic Death-supporting
confidence: 91%
“…It is well known that during cerebral ischemia, glutamate excitotoxicity occurs when a large amount of glutamate is released from brain tissue into the extracellular space, as documented by in vitro studies [18], in vivo animal studies [19], [20], and in ischemic patients [5], [21], [22]. However the mechanism throughout temperature modifies the brain glutamate release is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Cultures of rat primary neurons were prepared from embryonic day 18 Sprague-Dawley rats according to the method described by Antonelli et al [25]. Pregnant female Sprague-Dawley rats were killed by CO 2 .…”
Section: Methodsmentioning
confidence: 99%